Clinical application of a scale to assess genomic healthcare empowerment (GEmS): Process and illustrative case examples. Issue 1 (11th June 2021) - McConkie‐Rosell, Allyn; Schoch, Kelly; Sullivan, Jennifer; Spillmann, Rebecca C.; Cope, Heidi; Tan, Queenie K.‐G.; Palmer, Christina G. S.; ,; Hooper, Stephen R.; Shashi, Vandana
Abstract: The Genome Empowerment Scale (GEmS), developed as a research tool, assesses perspectives of parents of children with undiagnosed disorders about to undergo exome or genome sequencing related to the process of empowerment. We defined genomic healthcare empowerment as follows: perceived ability to understand and seek new information related to the genomic sequencing, manage emotions related to the diagnostic process and outcomes, and utilize genomic sequencing information to the betterment of the individual/child and family. The GEmS consists of four scales, two are primarily emotion‐focused (Meaning of a Diagnosis, and Emotional Management of the Process) and two are action‐oriented (Seeking Information and Support, and Implications and Planning). The purpose of this research was to provide a strategy for interpreting results from the GEmS and present illustrative cases. These illustrations should serve to facilitate use of the GEmS in the clinical and research arena, particularly with respect to guiding genetic counseling processes for parents of children with undiagnosed conditions.